Kedudukan Mengenai Anak Sah dan Tidak Sah dalam Perkawinan Menurut Hukum Positif di Indonesia - Muhammad Rizky Aditia Nugraha (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
The position of children in marriage plays an important role in family law because it is related to the legal status and fulfillment of children's civil rights. Differences in regulations regarding legitimate children and children born out of wedlock in Indonesian positive law create legal uncertainty, particularly regarding civil relations with biological fathers. This study aims to analyze the legal status of legitimate children and illegitimate children and the changes in the legal paradigm following Constitutional Court Decision Number 46/PUU-VII/2010. This study uses normative legal methods with a statutory and conceptual approach. The results show that before the Constitutional Court decision, illegitimate children only had a civil relationship with their mother and their mother's family, whereas after the decision, illegitimate children can have a civil relationship with their biological father as long as the blood relationship can be legally proven. This decision confirms legal reform efforts to guarantee protection and legal certainty for children without discrimination based on birth status.